Sea buckthorn: A wonder bush - Singh, Indra Pratap; Singh, Vivek; Sood, Rhitisha; Singh, Rajat (Indian Farming, 2022)
Sea buckthorn (Hippophae L.) is a wonderful plant found in the Himalayan region with multiple pharmacological and commercial benefits. This deciduous shrub belongs to the family Elaeagnaceae and has been used over centuries as food and traditional medicine. A unique mixture of bioactive compounds is present throughout the plant, especially in fruits, which are known as sea berry or siberian pineapple. Sea buckthorn is a rich source of both lipophilic and hydrophilic antioxidants. In vitro and in vivo studies have shown a wide range of beneficial anti-inflammatory, anticarcinogenic, antioxidant and anti-atherosclerotic properties in juices, jams and oil derived from it. It is a valuable, multipurpose plant extensively grown in Asia, Europe and Canada. In order to use it in the best way for products of human nutrition, it is necessary to recognize its positive aspects and to eliminate the negative ones.